HUBUNGAN ASUPAN NUTRISI DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI - Azizatul Hamidiyah (LPPM Universitas Abdurrab, 2020)
Preliminary studies conducted previously at the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School showed that the majority of female students suffered from anemia as many as 29 out of 41 people (70.7%). This certainly can harm adolescents because it can cause a decrease in reproductive health, stunted development including intelligence, decreased ability and concentration of learning. The purpose of this study was to determine the relationship of nutritional intake with the incidence of anemia in young women at the Salafiyah Syafi'iyah Islamic Boarding School Sukorejo Situbondo. This research used quantitative research with analytical research methods. Data collection was performed using nutritional recall. The instrument used was an observation sheet. Data analysis was performed using a nutri survey and the chi-square statistical test. The population in this study were all santri in the Ma'Had Aly boarding school of Salafiyah Syafi’iyah Sukorejo boarding school, the sample in this study amounted to 86 respondents. From the results of the study showed the results of P-Value 0.029 with a significant level of 0.05 then H0 was rejected, meaning that there is a significant relationship between nutritional intake and anemia in young women. Keywords: Nutrition, Anemia, Young Women